2014
DOI: 10.1186/1744-9081-10-28
|View full text |Cite
|
Sign up to set email alerts
|

Intra-hippocampal administration of ZIP alleviates depressive and anxiety-like responses in an animal model of posttraumatic stress disorder

Abstract: BackgroundGiven that impairment of fear extinction has been implicated in the pathogenesis of posttraumatic stress disorder (PTSD), effective pharmacological interventions that facilitate fear extinction may provide alternative strategies to conventional treatment. It is generally accepted that the zeta inhibitory peptide (ZIP), a controversial inhibitor of protein kinase M zeta (PKMζ), could erase certain types of previously established long-term memories. However, it is unclear whether ZIP administration may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…In this study, rats exposed to RSPS paradigm exhibited PTSD-like behaviors as In the OF, EPM and MWM test, the RSPS group rats showed a significant anxiety-like behaviors and cognitive impairments compared with controls after RSPS exposure, which was consistent with our and other previous studies [30,32,33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, rats exposed to RSPS paradigm exhibited PTSD-like behaviors as In the OF, EPM and MWM test, the RSPS group rats showed a significant anxiety-like behaviors and cognitive impairments compared with controls after RSPS exposure, which was consistent with our and other previous studies [30,32,33].…”
Section: Discussionsupporting
confidence: 93%
“…The apparatus was made with black Plexiglas measuring 50 × The elevated plus maze (EPM) test was performed as previously described [32]. Morris water maze (MWM) was performed to evaluate the rat spatial learning and memory.…”
Section: Behavior Testsmentioning
confidence: 99%
“…Several previous studies have observed behavioral effects of SPS that persist for several weeks. Increased anxiodepressive behavior is seen shortly after SPS and persists for at least 2-3 weeks (Ji et al, 2014;Khan & Liberzon, 2004;Lin, Tung, & Liu, 2016;Miao et al, 2014;Patki et al, 2014;Peng et al, 2010;Takahashi, Morinobu, Iwamoto, & Yamawaki, 2006), consistent with the increase in anxietylike behavioral changes observed here 1-2 weeks after stress. We found that elevated plus maze behavior and NSF returned to normal within 5 weeks of SPS in normal (wild type) rats.…”
Section: Long-term Effects Of Acute Stresssupporting
confidence: 86%
“…The current findings indicate that cells born up to a week after a 1‐day stress continue to show decreased survival. L‐type calcium channels containing the Ca V 1.2 subunit, which are upregulated in the hippocampus following SPS and chronic stress and have been implicated in PTSD (Ji et al, ; Krzyzewska et al, ; Maigaard, Hageman, Jørgensen, Jørgensen, & Wörtwein, ), may be an important part of the mechanism regulating the survival of new neurons following SPS. A recent study found that cells born at the end of chronic stress period showed increased survival relative to cells born in unstressed rats (De Miguel, Haditsch, Palmer, Azpiroz, & Sapolsky, ), suggesting that the removal of stress may have a positive effect on survival of a cohort of neurons maturing during the poststress recovery period.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plus maze test. The elevated plus maze (EPM) test was performed after OFT as previously described (28). Briefly, the EPM apparatus is made up of two opposing open and two opposing closed arms (50 cm arms, 50 cm off the ground).…”
Section: Behavioral Testsmentioning
confidence: 99%